Polymorphisms at 16p13 are associated with systemic lupus erythematosus in the Chinese population. Issue 1 (30th August 2010) - Zhang, Zheng; Cheng, Yilin; Zhou, Xueya; Li, Yang; Gao, Jinping; Han, Jianwen; Quan, Cheng; He, Sumin; Lv, Yongmei; Hu, Dayan; Zhu, Kunju; Sun, Liangdan; et al.
Abstract : Background: Chromosomal region 16p13 has been reported to harbour variants associated with several autoimmune diseases, including type I diabetes, rheumatoid arthritis and multiple sclerosis. Objective: To test whether variants in the 16p13 region are also associated with systemic lupus erythematosus (SLE) by performing a candidate locus study in the Chinese Han population. Methods: Tag single nucleotide polymorphisms (SNPs) encompassing 50 kb upstream and downstream of the 250 kb linkage disequilibrium block, previously implicated in several autoimmune diseases, were analysed in 1047 patients with SLE and 1205 controls. The SNP showing the strongest association with SLE was then replicated in an independent cohort of 1643 cases and 5930 controls. Results and conclusions: The association between SNP rs12599402 and SLE reached the genome-wide significance level (p<5 × 10 −8 ). The SNP was likely to tag the same functional variant as previously reported in European populations. The results suggested that the chromosomal region at 16p13 contains common susceptibility genes for different immune-mediated disorders.